P285 Using transcranial direct current stimulation (tDCS) as a fatigue countermeasure. Issue 3 (March 2017) - McIntire, L.; McKinley, A.; Nelson, J.; Goodyear, C.
Abstract : Introduction: Long periods of sustained wakefulness are common in certain professions such as medicine, transportation, and military operations. These professions also carry a high-level of risk when performance on the job is not at its best. Caffeine is a common countermeasure used to combat the degradations in performance due to sleep deprivation but the effects are short lasting. Therefore, it is necessary to investigate other forms of fatigue countermeasures. Objectives: Previously, we found that transcranial direct current stimulation (tDCS) in the middle of the night (0400) during 26 h of sustained wakefulness provided a performance and mood benefit that lasted at least 6 h. Caffeine only provided 2 h of benefit. In this study, we examined the differences between stimulation early into the night shift (1800) versus in the middle of the night (0400) and the duration of benefit. These results were compared to a caffeine and control groups. Patients and methods: Five groups of ten participants in each received either active tDCS and placebo gum at 1800, caffeine gum with sham tDCS at 1800, active tDCS and placebo gum at 0400, caffeine gum with sham tDCS at 0400, or sham tDCS with placebo gum at 1800 and 0400 during 36-h of sustained wakefulness. Participants completed a vigilance task, a working memory task, a psychomotor vigilance task (PVT), and a procedural game beginning at 1800 h and continued every two hours throughout the night until 1900 the next day. Results: tDCS dosed at 1800 provided 24 h of improved reaction times compared to the control group. Caffeine produced faster reactions times also compared to the control group but for half the duration than the tDCS group. The tDCS group also had higher accuracy and lower lapses in attention than the control group throughout the vigil. Early administration also resulted in improved mood ratings for the tDCS group. When dosing at 0400, the tDCS group had similar reaction time and accuracy benefits as the group dosed at 1800. The 0400 dosing of tDCS also had higher accuracy than the control group throughout the rest of the vigil for the short-term memory task. Conclusions: In conclusion, we believe tDCS could be a powerful fatigue countermeasure. The effects appear to be more beneficial than caffeine because they are longer lasting and mood remains more positive.